1997
DOI: 10.1074/jbc.272.10.6416
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Definition of a Novel Human Galectin Which Is Immunogenic in Patients with Hodgkin's Disease

Abstract: Using autologous serum for the immunoscreening of a cDNA expression library derived from tissue involved by Hodgkin's disease, a new 36-kDa protein with the characteristics of galectins (S-type lectins) was detected. Sequence analysis of the cDNA clone HOM-HD-21 revealed two homologous motifs known as lectin domains with galactoside binding capacity. The two domains are linked by a stretch of about 30 amino acid residues and share a sequence homology of 39%. While the N-terminal lectin domain shows merely mode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
139
0
2

Year Published

2000
2000
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 221 publications
(143 citation statements)
references
References 35 publications
1
139
0
2
Order By: Relevance
“…Galectin-7, which is highly inducible by p53 (23) and normally expressed in stratified epithelia, is down-regulated in squamous cell carcinomas (36). Galectin-8 is overexpressed in prostate cancer (37), and galectin-9 is overexpressed in Hodgkin's lymphomas (38,39). Whether the altered expression of galec-tins contributes to the neoplastic transformation or is a consequence of the transformation awaits elucidation.…”
mentioning
confidence: 99%
“…Galectin-7, which is highly inducible by p53 (23) and normally expressed in stratified epithelia, is down-regulated in squamous cell carcinomas (36). Galectin-8 is overexpressed in prostate cancer (37), and galectin-9 is overexpressed in Hodgkin's lymphomas (38,39). Whether the altered expression of galec-tins contributes to the neoplastic transformation or is a consequence of the transformation awaits elucidation.…”
mentioning
confidence: 99%
“…10 Recent studies suggested that galectin-9 is a modulator of immune functions; it induces chemotaxis of eosinophils 11 and apoptosis of thymocytes, suggesting a possible role in the process of negative selection occurring during T-cell development. 12 With the objective of finding newer agents for the treatment of ATL, the present study was designed to investigate the antitumor potential of galectin-9 on HTLV-I-infected T-cell lines and primary ATL cells in vitro and in vivo, and the possible mechanisms involved in such antitumor activities.…”
mentioning
confidence: 99%
“…Galectin-9 has been detected extracellularly and intracellularly, and the expression of the protein is widely distributed in tissues (27,28). Indeed, the available results suggest that galectin-9 expression is frequently altered when comparing tumor tissue with normal tissue (29).…”
Section: Discussionmentioning
confidence: 99%